Strategi Pengembangan Usaha Mikro Kecil Menengah (UMKM) Berbasis Ekonomi Kreatif di Kecamata Baros Kabupaten Serang - Ratu Sofyatus Solehah; Uu Mutafakkiroh; Egi Abdul Aziz; Muhamad Raefi; Surya Alam (CV. ALIM'SPUBLISHING, 2026)
Baros District has the potential for creative economy-based Micro, Small, and Medium Enterprises (MSMEs) products that need to be strengthened, including products from the agricultural, livestock, crafts, food, and various other types of trade sectors. This study aims to analyze and assess the steps for developing creative economy-based MSMEs in Baros District, located in Serang Regency, Banten. The method applied is a qualitative approach through observation, interviews, document collection, and using a SWOT Matrix analysis to identify the strengths, weaknesses, opportunities, and challenges faced in developing creative economy-based MSMEs in Baros District, Serang Regency, Banten. Data sources used include the Head of Baros District, local village heads, academics, MSME actors, employees from the Serang Regency MSME Office, and MSME observers. This study lasted for one year. The appropriate strategy for developing MSMEs in Baros District is the SO (Growth) strategy, which utilizes existing strengths to increase competitiveness. The research revealed that MSMEs operating in the creative economy sector in Baros District still face various challenges in developing their businesses, such as limited capital, the use of simple production equipment, suboptimal marketing, a shortage of skilled labor, and limited use of technology and copyright registration for their products.